Scientificity of foresight: discussions on the subject of study - Chung Pinzás, Alfonso Ramón (2012)
This paper focus the problem related to the scientific character of the prospective, especially in its study object, so the problem is: Is the prospective a science?. The answer of this problem it is planted in three parts: first a short review by the origins of the futurology, then the future conception to the prospective and at the end it focus in its study object; everything based in a bibliographic research.